PENDEKATAN LAYANAN ANAK BERKEBUTUHAN KHUSUS DALAM PROSES PEMBELAJARAN DI SEKOLAH DASAR - Fitrianingrum, Rafa; Kartika, Elvira; Rizkita, Indra; Andriani, Opi (Jurnal Pendidikan Vokasi dan Seni, 2023)
Special needs education poses a challenge in the realm of education, as not all schools are willing to accept children with special needs into their educational environments. The implementation of special needs education in Indonesia takes two forms: segregative and mainstream. Educators dealing with special needs children often experience emotional pressures, making it crucial to employ an approach that aids educators in managing their emotions. This paper aims to elucidate the Service Approach for Children with Special Needs in the Learning Process at Elementary Schools, utilizing a literature review method by analyzing various relevant sources. There are generally two approaches to educational services for children with special needs: group/classical approach and individual approach.